2019
DOI: 10.1002/1873-3468.13310
|View full text |Cite
|
Sign up to set email alerts
|

TDP‐43 accelerates deadenylation of target mRNAs by recruiting Caf1 deadenylase

Abstract: TAR DNA‐binding protein 43 (TDP‐43) is an RNA‐binding protein, whose loss‐of‐function mutation causes amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration. Recent studies demonstrated that TDP‐43 binds to the 3′ untranslated region (UTR) of target mRNAs to promote mRNA instability. Here, we show that TDP‐43 recruits Caf1 deadenylase to mRNA targets and accelerates their deadenylation. Tethering TDP‐43 to the mRNA 3′UTR recapitulates destabilization of the mRNA, and TDP‐43 accelerates their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…1C), suggesting a strong preference of TDP-43 for 3′ UTR binding. This general 3′ UTR preference agrees with a previous publication (18) and has also been described for a handful of TDP-43 specific target mRNAs (19,35,36). The 3′ UTR binding also coincides with the proposed role of TDP-43 as an RNA stability and translational regulator (37,38).…”
Section: Tdp-43 Rna Targets Are Involved In Multiple Signaling Pathwasupporting
confidence: 90%
“…1C), suggesting a strong preference of TDP-43 for 3′ UTR binding. This general 3′ UTR preference agrees with a previous publication (18) and has also been described for a handful of TDP-43 specific target mRNAs (19,35,36). The 3′ UTR binding also coincides with the proposed role of TDP-43 as an RNA stability and translational regulator (37,38).…”
Section: Tdp-43 Rna Targets Are Involved In Multiple Signaling Pathwasupporting
confidence: 90%
“…Given the high conservation between murine and human 3′UTR sequences, here we showed that TDP-43 binding to human GRN mRNA is conserved and that TDP-43 depletion upregulates GRN gene expression, suggesting that TDP-43-mediated regulation of GRN mRNA instability is also likely to be maintained in humans. Indeed, recent findings have demonstrated that TDP-43 promotes GRN mRNA instability by acting on the deadenylation process in human cell models [33]. In rodent and human models, TDP-43 is known to regulate the stability of other mRNAs, with either destabilizing ( VEGF and Tau ) [7,34] or stabilizing ( NEFL , HDAC6 and Add2 ) [35,36,37] effects.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between TDP-43 and GRN however, is not straightforward. While studies have demonstrated that TDP-43 binds to the 3 untranslated region of GRN mRNA, promoting mRNA instability (Colombrita et al, 2012;Fukushima et al, 2019), GRN protein levels were not decreased. The observed difference in transcript and protein levels could be explained by the concurrent effect of TDP-43 on SORT1 mRNA (Gumina et al, 2019).…”
Section: Rna-binding Proteinsmentioning
confidence: 91%